Three-Dimensional Printed Model-Assisted Screw Installation in Treating Posterior Atlantoaxial Internal Fixation - Minyi Yang (Nature Portfolio, 2018)
Abstract The aim of this study was to evaluate the efficacy and feasibility of a life-size 3-dimensional printing assisted posterior internal fixation. We performed a retrospective review of 138 patients who received posterior atlantoaxial internal fixation from October 2009 to March 2015 with a minimum follow-up period of 12 months. Group A included 76 patients who received the conventional free-hand technique. Group B included 62 patients who were treated with internal fixation assisted by 3D printing. The placement accuracy of the screw was evaluated in the computed tomography images according to the methods of Hojo and clinical outcomes were evaluated using the visual analogue scale, the Japanese Orthopedic Association Score, and the Neck Disability Index score. There were no significant differences in the clinical results at any of the follow-up time points regarding the JOA, VAS, or NDI scores between two group. However, compared to Group A, Group B had better results for screw installation (P = 0.003), shorter surgery time (P = 0.001), and less blood loss (P = 0.037). Compared to the conventional free-hand technique, 3D printed model–assisted is helpful to screw placement in atlantoaxial internal fixation, which can be used as a common tool to provides important guidance for upper cervical surgery.